"Hatred Is Tremendous Cement": Complexity Science and Political Consciousness in Chaotic Times. (3rd July 2019) - Nelson, Elizabeth Èowyn
Abstract : The relationship between love and hatred is evident in Greek epic and myth, Greek philosophy, and in Jungian theory. This article examines the cement of hatred in light of the 2016 election of Donald Trump. It briefly discusses Andrew Samuel's "action ethos" as a Jungian political response; Jung's thoughts on emotion, conflict, and consciousness as they pertain to individuation; and the notion of the cultural complex developed by Singer and Kimbles. This framework is deepened with a short meditation on mythic Chaos and its close relationship with Eros as a generative, formative, and connecting principle. The last half of the article reaches across a disciplinary boundary to employ three principles of complexity science to understand Trump's election and the world it has shaped: unpredictability, bifurcation, and autopoeisis. How might complexity theory help us to think differently about the eros of hatred in chaotic times, and what political actions might these thoughts inspire?